Penggunaan Etnomatematika Pada Batik Paoman Dalam Pembelajaran Geomteri Bidang di Sekolah Dasar - Sudirman Sudirman; Aloisius Loka Son; Rosyadi Rosyadi (IndoMath: Indonesia Mathematics Education, 2018)
This study aims to explore the ethnomatematics contained in Batik Paoman Indramayu and apply it to the learning of geometry field in elementary school. This research is a qualitative research with ethnography approach, where the data collection technique is done by library study, observation, interview, field note, and documentation. Interviews were conducted on two batik entrepreneurs and an embroidered entrepreneur. Based on the results of research data collection obtained 7 namely Parang Teja, Obar Abir, Biskuit Sawat, Serujing, Matahari, Siled and Banji Tepak. The concept of elementary geometry in the primary school that is on the paoman batik motif is the concept of point, straight line, curve line, zigzag line, line height, parallel line, angle, triangle, rectangle, fold symmetry, rhombus.Paoman batik motif that has the concept of geometry for elementary school, of course can be used in the pursuit of geometry fields such as on line recognition, angle recognition, and simple flat wake recognition.